The influence of peri-conception and first trimester dietary restriction of protein in cattle on meat quality traits of entire male progeny. (November 2016) - Alvarenga, Tharcilla I.R.C.; Copping, Katrina J.; Han, Xuemei; Clayton, Edward H.; Meyer, Richard J.; Rodgers, Raymond J.; McMillen, I. Caroline; Perry, Viv E.A.; Geesink, Geert
Abstract: Primiparous Santa Gertrudis heifers were used to evaluate the effects of gestational dietary protein content on meat quality traits of 20 month old bull progeny (n = 40). At − 60 d before AI, heifers were randomly allocated to HIGH or LOW protein diet (HPERI and LPERI). From 24 dpc, half of each treatment group changed to an alternative post-conception HIGH or LOW protein diet (HPOST and LPOST). LPERI and LPOST diets resulted in higher shear force of the semitendinosus muscle than HPERI ( P = 0.053) and HPOST ( P = 0.003), respectively. Heat-soluble collagen in the semitendinosus muscle was lower ( P = 0.019) for LPERI than HPERI. Collagen and tenderness of the longissimus muscle were not affected by dam nutrition ( P > 0.05). Color, pH, sarcomere length, cooking loss, compression values, desmin and troponin-T degradation, fiber type, intramuscular fat and polyunsaturated fatty acid content were not affected by dam nutrition during the peri-conception and first trimester gestational period ( P > 0.05).